Aspek Perkembangan Manajemen Pembelajaran: Active Learning - M. Shohibul Aziz (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2018)
The development of education in Indonesia is basically always interesting to observe and discuss. The concrete challenge lies in how to prepare human resources in this case teachers to manage learning. Because quality learning other than highly dependent on student motivation, also depends on the creativity of teachers.In its development, many models, strategies and learning techniques that can be selected as an alternative teacher to manage learning as well as develop creativity. One of the learning models is Active Learning or active learning.This active learning is based on the epistemology of constuctivism that emphasizes how one learns. How one develops his understanding and knowledge of the world around him by recognizing the objects around him that are reflected through his experience. When discovering something new, it is hoped that someone can reconstruct it with initial ideas and previous experiences.In line with the above basic concept, in Government Regulation no. 19 on National Education Standards, article 19, paragraph (1) states that